2004
DOI: 10.1021/jm049681p
|View full text |Cite
|
Sign up to set email alerts
|

NO-Sartans:  A New Class of Pharmacodynamic Hybrids as Cardiovascular Drugs

Abstract: The aim of this work was to develop lead pharmacodynamic hybrids, NO-sartans, possessing the characteristics of a typical AT1-antagonist and of a "slow NO donor", by adding NO-donor side chains to losartan. These new compounds, 2a and 2b, displayed vasorelaxing effects, due to the release of NO, and antagonized the vasocontractile effects of angiotensin II, with potency values similar to that of losartan. In vivo, the antihypertensive effects of 2a were similar to those of losartan and captopril.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…83 A group from the University of Pisa in Italy has described the synthesis and characterization of NO-donor analogs of losartan and its active metabolite EXP-3174. 84,85 The bifunctional nature of the compounds was assessed using in vitro organ bath preparations of rat endothelium-denuded aortic rings. ARB-NO hybrids mediated concentration-dependent relaxation of aortic rings pre-contracted with KCl, which was blocked in the presence of ODQ, an inhibitor of guanylate cyclase, showing the activation of the NO-cGMP pathway by the compound.…”
Section: Next Generation Arbs That Are No Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…83 A group from the University of Pisa in Italy has described the synthesis and characterization of NO-donor analogs of losartan and its active metabolite EXP-3174. 84,85 The bifunctional nature of the compounds was assessed using in vitro organ bath preparations of rat endothelium-denuded aortic rings. ARB-NO hybrids mediated concentration-dependent relaxation of aortic rings pre-contracted with KCl, which was blocked in the presence of ODQ, an inhibitor of guanylate cyclase, showing the activation of the NO-cGMP pathway by the compound.…”
Section: Next Generation Arbs That Are No Donorsmentioning
confidence: 99%
“…A group from the China Pharmaceutical University in Nanjing, China, has explored NO-releasing derivatives of telmisartan using an approach similar to that of Breschi et al [84][85][86] The lead compound WB1106 was found to have dual activity in isolated rat aortic preparations and significantly reduced angiotensin II-mediated pressor responses in normotensive rats. WB1106 lowered blood pressure in spontaneously hypertensive rats to the same extent as telmisartan, but, in contrast to telmisartan, increased aortic cGMP levels, with similar magnitude as the ACE inhibitor, fosinopril.…”
Section: Next Generation Arbs That Are No Donorsmentioning
confidence: 99%
“…Indeed, NO-releasing losartan and NO-releasing telmisartan have been synthesized and demonstrated to have superior cardiovascular effects when compared with those of the original ARBs in ex vivo and in vivo preclinical studies. [7][8][9] Interestingly, however, clinical trials have not yet been reported for NO-releasing ARBs.…”
Section: Article P656mentioning
confidence: 99%
“…In the thriving panorama of cardiovascular NO-releasing drugs, a new class of potential antihypertensive agents, NOSartans, (pharmacodynamic hybrids which show the dual profile of a typical AT1-antagonist and of a slow NO-donor) has been recently reported [205]. Like ACE-inhibitors, sartans, such as losartan, act on the RAS, but not interfering with the ACE; in fact, their mechanism of action consists of the antagonism of the angiotensin II receptor AT1.…”
Section: No-sartansmentioning
confidence: 99%